His bundle pacing: a new look at the method - N. A. Prikhodko; T. A. Lyubimtseva; S. V. Gureev; V. K. Lebedeva; D. S. Lebedev (Российский кардиологический журнал)
His bundle pacing (HBP) implements physiological impulse propagation along the cardiac conduction system and can serve as an analogue of both right ventricular and biventricular pacing. This review highlights clinical anatomy issues related to HBP; the technique of lead implantation in the His position is considered. We also describe the electrophysiological basis of HBP, possibilities of lead extraction, indications for implantation, and prospects for further development of the technique. HBP is a promising direction in cardiology, which in the future may fundamentally change the algorithms for managing patients with heart failure and conduction disorders.